Talar beak-induced intermittent ischemia of the foot - Rotmans, Joris I. (J Vasc Surg Cases Innov Tech, 2020)
A 44-year-old man presented with symptoms of intermittent ischemia of the right foot. Computed tomography scanning of the right foot revealed a talar beak that had a close anatomic relation with the dorsalis pedis artery. Duplex ultrasound performed during a symptomatic episode confirmed ischemia induced by severe vasospasm of the dorsalis pedis artery that normalized 30 minutes later. The talar beak was removed by open surgery that resulted in complete resolution of the patient's symptoms. A talar beak should be considered in intermittent ischemic complaints of the foot in patients without atherosclerosis.